(untitled) (International Journal of Innovative Research in Engineering & Management, 2021)
Business is not a simple for any one as there are many companies exited in the market in various area. One need to prepare their preparation and plans carefully so that they may compete in highly turbulent market and generate profit for their organisation. The current research has been prepared to figure out the difference and similarities between the marketing strategy of an organisation who are engaged into pure industrial operations and a non-profit organisation. The marketing tactics are important elements which may be determined in preparation before start the real activity. The basic aim of an NGO is to being revolutionary changes in the society as well as in mind of people but they need fund to carried out their activities and they have to options for this, first generate their own money through some business activities and second solely depends upon the fund received from other organisation. The future consequence of this research is to discover the answer and comparison as well for marketing planning of NGO in comparison to pure industrial organisation.